Project tasks effectiveness based on potential of student’s region on student engagement - ., Syahril (Opción, 2020)
This study aimed to investigate the following: „what can the project task of region potential do to make students possible act more active with the high involvement of learning?‟ This study used proactive action research that focused on a new way to improve students‟ engagement. The result of this study shows that the implementation of a project-based on the potential of the student‟s region was effective to make students engage with the learning process. In conclusion, the factor that makes high students‟ engagement was the project task that has been done, because it was very useful for their region